Finding the Corridor Potential between Protected Areas in a Fragmented Landscape, Gunungkidul Regency, Indonesia - Panuntun, Madina Dwi (Sciendo, 2023)
Fragmentation impacts disconnecting protected areas in Gunungkidul Regency, namely Bunder Forest Park (BFP) and the Paliyan Wildlife Reserve (PWR). This also decreases the carrying capacity in PWR, degrading the Long-Tailed Macaque (LTM) habitat. Therefore, this research aims to analyze the landscape structure between Protected areas, the habitat suitability of LTM in Gunungkidul Regency, and determine connectivity potential as an environmental management strategy. applied for this research to investigates the structure and fragmentation using Fragstat 4.2 and ArcGIS 10.8 software. Meanwhile, scoring and weighting methods analyze the LTM habitat, while Least Cost Patch Analysis (LCPA) supported by ArcGIS 10.8 determine the corridor. The results showed that the research land cover changed from 1999-2021. Agriculture, scrubs, and settlements are the dominant land cover suspected to cause forest fragmentation. Based on the habitat suitability analysis using parameters such as land cover, vegetation density, slope, altitude, distance from the river, and sources of threats, most of the research area is intermediate habitat suitability class. These findings can be integrated to determine connectivity between protected areas as one of the environment management strategies. Good forest cover can be used to designate a corridor that has the greatest potential to be developed between BFP and PWR and should be maintained as a wildlife crossing. © 2023 Madina Dwi Panuntun et al., published by Sciendo.